Echo in the canyon - Slater, Andrew ca. 20. Jh; Barrett, Eric ca. 20. Jh; Darrin, Pat ca. 20. Jh; Kibbe, Kyle; Turnbull, Brent; Burberry, Vance ca. 20. Jh; Waller, Garry ca. 20. Jh; Dylan, Jakob 1969- (2020)
"Echo In The Canyon celebrates the explosion of popular music that came out of LA’s Laurel Canyon in the mid-60s as folk went electric and The Byrds, The Beach Boys, Buffalo Springfield and The Mamas and the Papas gave birth to the California Sound. It was a moment (1965 to 1967) when bands came to LA to emulate The Beatles and Laurel Canyon emerged as a hotbed of creativity and collaboration for a new generation of musicians who would soon put an indelible stamp on the history of American popular music." [jpc.de]
Original: USA 2018
Bildformat 16:9
Keywords: Geschichte 1961-1970; Rockmusik; Musikleben; Laurel Canyon -- Los Angeles, Calif.; Film; DVD-Video